Positive pole piece, battery monomer, battery and electric device

By using high specific surface area conductive agents and sodium supplementation agents in the positive electrode film layer of sodium ion battery, the problems of low circulation stability and Coulomb efficiency of sodium ion battery are solved, and the battery performance and energy density are improved.

CN119153619APending Publication Date: 2024-12-17CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202310705837.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The cycle stability and Coulomb efficiency of existing sodium ion batteries are low, mainly due to the irreversible consumption of sodium ions at the interface between the electrode and the electrolyte, resulting in the degradation of battery performance.

Method used

Add a first conductive agent and sodium replenishing agent with a specific surface area of ​​no less than 600m2/g to the positive electrode film layer. By increasing the contact site between the conductive agent and the sodium replenishing agent, the oxidation voltage of the sodium replenishing agent is reduced, and the operation of the battery is carried out. Voltage compatibility, thereby improving battery cycling performance and Coulomb efficiency.

Benefits of technology

It effectively improves the circulation performance and Coulomb efficiency of sodium ion batteries, reduces the irreversible consumption of sodium ions, extends the service life of the battery and increases the energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153619A_ABST
    Figure CN119153619A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a positive pole piece, a battery monomer, a battery and an electric device. The positive pole piece comprises a positive current collector and a positive film layer arranged on at least one side of the positive current collector; the positive electrode film layer comprises a positive electrode active material, a sodium supplementing agent and a first conductive agent; wherein the specific surface area of the first conductive agent is not less than 600m < 2 > / g. According to the technical scheme, the coulombic efficiency and the cycle performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet, a battery cell, a battery and an electrical device. Background Art

[0002] In recent years, with the gradual development and application of lithium-ion batteries from portable electronic devices to high-power electric vehicles, large-scale energy storage power stations and smart grids, the demand for lithium metal in various industries has been increasing. However, with the reduction of lithium metal resources and the increasing difficulty of mining, the current lithium metal resources can no longer meet the needs of the lithium battery industry. Sodium, which is in the same main group as lithium, has similar chemical properties to lithium and is abundant in reserves. Therefore, sodium-ion batteries with similar working principles to lithium-ion batteries are currently being developed, and it is expected that sodium-ion batteries will serve as an important supplement to lithium-ion batteries in large-scale energy storage applications.

[0003] Therefore, how to improve the cycle performance and coulombic efficiency of sodium-ion batteries is an urgent problem to be solved. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode plate, a battery cell, a battery and an electrical device, which can improve the cycle performance and coulombic efficiency of the battery.

[0005] The first aspect of the present application provides a positive electrode sheet, comprising: a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector; the positive electrode film layer comprises a positive electrode active material, a sodium supplement, a first conductive agent and a second conductive agent; wherein the specific surface area of ​​at least one of the first conductive agent and the second conductive agent is not less than 600 m 2 / g.

[0006] In the embodiment of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer, and the positive electrode film layer includes a positive electrode active material, a sodium supplement, and a first conductive agent; further, the specific surface area of ​​the first conductive agent is not less than 600m 2 / g. A sodium supplement is added to the positive electrode film layer, which can effectively supplement the sodium ion loss caused by some irreversible reactions in the battery, and help form a better and more stable SEI film in the battery, thereby improving the coulombic efficiency and cycle performance of the battery. By adding a first conductive agent to the positive electrode film layer, wherein the specific surface area of ​​the first conductive agent is not less than 600m 2 / g, the first conductive agent or the second conductive agent with a high specific surface area can have more contact sites with the sodium supplement agent, thereby reducing the charge transfer and polarization resistance, and further reducing the oxidation voltage of the sodium supplement agent so that the effective voltage of the sodium supplement agent is compatible with the normal operating voltage of the battery, thereby effectively improving the cycle performance and coulombic efficiency of the battery.

[0007] In a possible implementation manner, the specific surface area of ​​the first conductive agent is 600-1600 m 2 / g, optionally, the specific surface area of ​​the first conductive agent is 1200-1500m 2 / g.

[0008] In the embodiment of the present application, the sodium supplement agent and the conductive agent with a high specific surface area are used together, so that the effective voltage of the sodium supplement agent can match the battery operating voltage, thereby improving the coulombic efficiency and cycle performance of the battery. 2 / g, especially 1200-1500m 2 / g, which can further ensure that the first conductive agent and the sodium supplement agent have more contact sites, and help to further reduce the oxidation voltage of the sodium supplement agent.

[0009] In a possible implementation, the first conductive agent includes at least one of a chain-shaped conductive agent or a grape-shaped conductive agent; optionally, the first conductive agent includes at least one of conductive carbon black and conductive graphite; optionally, the conductive carbon black includes at least one of acetylene black and Ketjen black.

[0010] In the embodiment of the present application, by using at least one of a chain-shaped conductive agent or a grape-shaped conductive agent as the first conductive agent, the contact form between the first conductive agent and the sodium supplementer is point-to-point, which can ensure that the first conductive agent and the sodium supplementer have more contact sites, thereby improving the effect of the first conductive agent on the sodium supplementer; further, using at least one of conductive carbon black and conductive graphite, which are more convenient to obtain, as the first conductive agent, especially acetylene black or Ketjen black as the first conductive agent, is conducive to wide application in industry.

[0011] In a possible implementation, when the first conductive agent includes conductive carbon black, the volume average particle size Dv50 of the first conductive agent is 20-60 nm. Optionally, the volume average particle size Dv50 of the first conductive agent is 30-50 nm.

[0012] In the embodiment of the present application, when conductive carbon black is used as the first conductive agent, the first conductive agent, that is, the volume average particle size Dv50 of these three materials is limited to 20-60nm, especially 30-50nm. The smaller particle size can make the first conductive agent contact with the sodium supplement more evenly.

[0013] In a possible implementation, when the first conductive agent includes conductive graphite, the volume average particle size Dv50 of the first conductive agent is 3-4 μm. Optionally, the volume average particle size Dv50 of the first conductive agent is 3.2-3.6 μm.

[0014] In the embodiment of the present application, when conductive graphite is used as the first conductive agent, by limiting the volume average particle size Dv50 of the first conductive agent, ie, the conductive graphite, to 3-4 μm, particularly 30-50 nm, the first conductive agent can be in more uniform contact with the sodium supplementer.

[0015] In a possible implementation, the positive electrode film layer further includes a second conductive agent, and the second conductive agent includes at least one of carbon fiber, carbon nanotube, ordered dielectric porous carbon, and graphene.

[0016] In the present application, when the specific surface area is 600-1600m 2 / g, especially 1200-1500m 2 When the first conductive agent of 100 g is added to the positive electrode film layer including the sodium supplement, the first conductive agent can reduce the oxidation potential of the sodium supplement so that the sodium supplement can function normally. By adding at least one of carbon fiber, carbon nanotube, ordered dielectric porous carbon, and graphene to the positive electrode film layer, the contact between the second conductive agent and the sodium supplement is point-line contact, which is conducive to further achieving voltage compatibility between the sodium supplement and the battery, thereby further improving the cycle performance and coulomb efficiency of the battery.

[0017] In a possible implementation manner, when the second conductive agent includes carbon nanotubes, the carbon nanotubes have a length of 0.5-30 μm, a diameter of 2-15 nm, and a specific surface area of ​​not less than 200 m 2 Optionally, the carbon nanotubes have a length of 0.5-10 μm, a diameter of 2-6 nm, and a specific surface area of ​​400-600 m 2 / g.

[0018] In a possible implementation manner, when the second conductive agent includes ordered mesoporous carbon, the ordered mesoporous carbon has a pore size of 2-50 nm and a specific surface area of ​​500-1500 m 2 / g, optionally, the ordered mesoporous carbon has a pore size of 3.2-6.6 nm and a specific surface area of ​​800-1300 m 2 / g.

[0019] In a possible implementation, when the second conductive agent includes graphene, the graphene has a thickness of 0.6-4 nm and a sheet diameter of 0.5-5 μm. Optionally, the graphene has a thickness of 1.5-3.2 nm and a sheet diameter of 0.5-3 μm.

[0020] In the embodiment of the present application, when the first conductive agent and the second conductive agent are used together to reduce the oxidation potential of the sodium supplement, the cycle performance and coulombic efficiency of the battery can be further improved. 2By limiting the performance parameters of the second conductive agent to the above range, the second conductive agent with better conductivity can better assist the first conductive agent, thereby further improving the performance of the battery.

[0021] In a possible implementation manner, the mass ratio of the first conductive agent to the second conductive agent is 1-49. Optionally, the mass ratio of the first conductive agent to the second conductive agent is 4-9.

[0022] In the embodiment of the present application, in order to further improve the performance of the battery, a mixed first conductive agent and a second conductive agent are used in the battery film layer to reduce the effective voltage of the sodium supplement. By limiting the mass ratio of the first conductive agent to the second conductive agent to 1-49, especially 4-9, the possibility of insufficient reduction of the effective voltage of the sodium supplement due to too little addition of the first conductive agent can be reduced.

[0023] In a possible implementation, based on 100 parts by weight of the positive electrode film layer, the sum of the weights of the first conductive agent and the second conductive agent is 0.1-5 parts by weight. Optionally, the sum of the weights of the first conductive agent and the second conductive agent is 0.5-3 parts by weight.

[0024] In the embodiment of the present application, by limiting the conductive agent, that is, the sum of the masses of the first conductive agent and the second conductive agent, to 0.1%-5%, especially 0.5%-3% of the positive electrode film layer, the effective voltage of the sodium supplement can be effectively reduced so that the sodium supplement can improve the cycle performance and coulombic efficiency of the battery, and the energy density of the battery will not be affected by the excessive proportion of the first conductive agent and the second conductive agent.

[0025] In a possible implementation, based on 100 parts by weight of the positive electrode film layer, the weight of the sodium supplement is 0.5-20 parts by weight. Optionally, the weight of the sodium supplement is 1-5 parts by weight.

[0026] In the embodiment of the present application, by limiting the sodium supplement to 0.5%-20%, especially 1%-5% of the positive electrode film layer, the sodium loss in the battery can be effectively compensated without affecting the mass proportion of the positive electrode active material due to excessive proportion.

[0027] In a possible embodiment, the sodium supplement includes at least one of the following inorganic sodium supplements or organic sodium supplements, the inorganic sodium supplement includes NaN3, Na2O2, Na2O, Na2CO3, NaNO2, NaBH4, NaNH2, Na2NiO2, NaCrO2, Na3P, Na2S, the organic sodium supplement includes CH3COONa, C7H6NNaO2, C 10 H 12 N2Na4O8、C 14 H18 N3Na5O 10 、Na a C b H c O d , 1≤a≤2, 2≤b≤6, 0≤c≤2, 2≤d≤6, optionally, the sodium supplement includes Na2C2O4.

[0028] In the embodiments of the present application, when at least one of the above-mentioned inorganic sodium supplement or organic sodium supplement is used as the sodium supplement, the sodium supplement can make up for the irreversible sodium ion loss of the battery during the cycle, and does not affect the potential of the positive electrode active material, thereby improving the coulombic efficiency and cycle performance of the battery. In particular, when the sodium supplement includes Na2C2O4, Na2C2O4 decomposes and releases sodium ions and gas during battery formation and charging. The gas generated by the decomposition can be removed in the formation stage, and the sodium ions generated by the decomposition can effectively solve the problem of low battery energy density and poor cycle stability caused by irreversible consumption of sodium ions, that is, it can improve battery performance and have no adverse effects on the environment and the battery.

[0029] In one possible implementation, the compaction density of the positive electrode sheet is 1.2-2.8 g / cm 3 Optionally, the compaction density of the positive electrode sheet is 1.6-2.3 g / cm 3 .

[0030] In the embodiment of the present application, the compaction density of the positive electrode sheet is limited to 1.2-2.8 g / cm 3 , especially 1.6-2.3g / cm 3 , which helps to further improve the energy density of the battery.

[0031] In a possible implementation, the thickness of the positive electrode plate is 50-90 μm. Optionally, the thickness of the positive electrode plate is 65-80 μm.

[0032] In the embodiments of the present application, by limiting the thickness of the positive electrode plate to 50-90 μm, especially 65-80 μm, it helps to further improve the energy density of the battery.

[0033] In one possible embodiment, the coating weight of the positive electrode sheet is 3.5-35 mg / cm 2 Optionally, the coating weight of the positive electrode sheet is 10-25 mg / cm 2 .

[0034] In the embodiment of the present application, the coating weight of the positive electrode sheet is limited to 3.5-35 mg / cm 2 , especially 10-25mg / cm 2, which helps to further improve the energy density of the battery.

[0035] In one possible embodiment, the positive electrode active material includes Na x R y (PO4) z (P2O7) k , wherein 1≤x≤7, 1≤y≤4, 1≤z≤2, 1≤k≤4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W and Pb.

[0036] In the embodiments of the present application, the use of the above materials as positive electrode active materials helps to further improve the energy density of the battery.

[0037] A second aspect of the present application provides a battery cell, comprising the positive electrode sheet according to any one of the embodiments in the first aspect of the present application.

[0038] In a possible implementation, the battery cell further includes a negative electrode plate, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector, and the negative electrode film layer includes a conductive agent.

[0039] A third aspect of the present application provides a battery, comprising a battery cell according to any one of the embodiments in the second aspect of the present application.

[0040] The fourth aspect of the present application provides an electrical device, comprising the battery according to the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0042] Figure 1 It is a schematic structural diagram of a positive electrode sheet according to an embodiment of the present application;

[0043] Figure 2 is a schematic diagram of a battery cell according to an embodiment of the present application;

[0044] Figure 3 is a schematic structural diagram of a battery cell according to an embodiment of the present application;

[0045] Figure 4 is a schematic diagram of a battery according to one embodiment of the present application;

[0046] Figure 5 is a schematic structural diagram of a battery according to one embodiment of the present application;

[0047] Figure 6 It is a schematic diagram of an electrical device according to one embodiment of the present application. DETAILED DESCRIPTION

[0048] The following describes the embodiments of the positive electrode sheet, battery cell, battery and electric device of the present application in detail with appropriate reference to the drawings, but there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0049] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a specific range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0050] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0051] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0052] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, and can be performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0053] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or comprised.

[0054] The terms "above", "below", "greater than" or "less than" as used in this application include the number, for example, "at least one" means one or more, and "at least one of A and B" means "A", "B" or "A and B".

[0055] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0056] The working principle of sodium batteries is similar to that of lithium batteries, that is, charging and discharging are achieved by using the insertion and extraction process of sodium ions between the positive and negative electrodes. Compared with lithium batteries, sodium batteries have the following advantages: (1) the reserves of metallic sodium are more abundant than those of metallic lithium, and the price advantage is greater; (2) at the same concentration, the conductivity of sodium salt is higher than that of lithium salt, so a lower concentration of electrolyte can be used, and the battery manufacturing cost is relatively low.

[0057] Similar to lithium batteries, the cycle life of sodium batteries is related to the stability of the interface (such as the electrode and electrolyte interface). The formation of the interface is often accompanied by the irreversible consumption of sodium ions, especially the interface between the negative electrode and the electrolyte. Because the SEI film formed when the battery is first charged and discharged will consume sodium ions, and this part of the consumption is irreversible. However, if too much sodium ions are consumed, it will have a greater impact on the performance of the battery. Therefore, how to reduce the irreversible consumption of limited sodium ions is the key to restricting the cycle stability and coulombic efficiency of sodium batteries.

[0058] In order to solve the above problems, the commonly used methods include spraying sodium powder, spraying organic sodium solution, positive electrode sodium supplementation additives, etc. Among them, adding sodium supplementation additives to the positive electrode has attracted attention due to its good effect and simple operation. However, the oxidation potential of some sodium supplements is relatively high, which is not compatible with the battery system, resulting in the inability of the sodium supplements to function. Therefore, how to achieve voltage compatibility between the sodium supplement and the battery system, thereby improving the coulombic efficiency and cycle performance of the battery, is a problem that needs to be solved urgently.

[0059] In view of this, the present application provides a positive electrode plate, the positive electrode plate comprising a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector. The positive electrode film layer comprises a sodium supplement and a first conductive agent, and further, the specific surface area of ​​the first conductive agent is not less than 600m 2 / g, sodium supplement helps to improve the cycle performance and coulomb efficiency of the battery, and the specific surface area is not less than 600m 2 / g of the first conductive agent can reduce the effective voltage of the sodium supplement agent and achieve voltage compatibility between the sodium supplement agent and the battery system, thereby effectively improving the cycle performance and coulombic efficiency of the battery.

[0060] The positive electrode sheet, battery cell, battery and electrical device of the present application are described below with reference to the accompanying drawings.

[0061] In addition, the technical solution of the present application is applicable to sodium ion batteries or sodium metal batteries, and the present application does not limit this; for the convenience of description, the following description will be given using sodium ion batteries as an example.

[0062] [Positive electrode]

[0063] The first aspect of the present application provides a positive electrode plate, Figure 1 Schematic diagram of the structure of the positive electrode sheet of one embodiment of the present application. Figure 1 As shown, the positive electrode sheet 121 includes a positive electrode current collector 122 and a positive electrode film layer 123 disposed on at least one side of the positive electrode current collector 122. The positive electrode film layer 123 includes a positive electrode active material, a sodium supplement, and a first conductive agent; wherein the specific surface area of ​​the first conductive agent is not less than 600 m 2 / g.

[0064] A first conductive agent is added to the positive electrode film layer 123, and the specific surface area of ​​the first conductive agent is not less than 600 m 2 / g, which can reduce the effective voltage of the sodium supplement and achieve voltage compatibility between the sodium supplement and the battery, thereby improving the coulombic efficiency and cycle performance of the battery.

[0065] Typically, a battery cell includes a positive electrode sheet 121, a separator, a negative electrode sheet, and an electrolyte. During the battery charge and discharge process, active ions are embedded and released back and forth between the positive electrode and the negative electrode. The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The separator is arranged between the positive electrode and the negative electrode, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0066] It should be noted here that the “positive electrode sheet” and “negative electrode sheet” mentioned in the embodiments of the present application refer to the positive electrode sheet 121 and the negative electrode sheet as a whole including active materials, current collectors or other additives.

[0067] The positive electrode sheet 121 includes a positive electrode current collector 122 and a positive electrode film layer 123 disposed on at least one surface of the positive electrode current collector 122, wherein the positive electrode film layer 123 includes a sodium supplement and a first conductive agent, wherein the specific surface area of ​​the first conductive agent is not less than 600 m 2 / g.

[0068] As an example, the positive electrode current collector 122 has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer 123 is disposed on any one or both of the two opposite surfaces of the positive electrode current collector 122 .

[0069] The sodium supplement is a substance that can supplement the sodium ions in the sodium ion battery. Specifically, the sodium supplement can be some organic or inorganic substances containing sodium ions. For example, it can be an oxide or sodium salt containing sodium.

[0070] In the above scheme, the positive electrode sheet 121 includes a positive electrode current collector 122 and a positive electrode film layer 123, and the positive electrode film layer 123 includes a positive electrode active material, a sodium supplement, and a first conductive agent; further, the specific surface area of ​​the first conductive agent is not less than 600m 2 / g. A sodium supplement is added to the positive electrode film layer 123, which can effectively supplement the sodium ion loss caused by some irreversible reactions in the battery, and help form a better and more stable SEI film in the battery, thereby improving the coulombic efficiency and cycle performance of the battery. By adding a first conductive agent to the positive electrode film layer 123, wherein the specific surface area of ​​the first conductive agent is not less than 600m 2 / g, the first conductive agent with a high specific surface area can have more contact sites with the sodium supplement agent, thereby reducing the charge transfer and polarization resistance, and further reducing the oxidation voltage of the sodium supplement agent to make the effective voltage of the sodium supplement agent compatible with the normal operating voltage of the battery, thereby effectively improving the cycle performance and coulombic efficiency of the battery.

[0071] In some embodiments, the specific surface area of ​​the first conductive agent is 600-1600 m 2 / g, optionally, the specific surface area of ​​the first conductive agent is 1200-1500m 2 / g.

[0072] In the above scheme, the sodium supplement agent and the conductive agent with a high specific surface area are used together, so that the effective voltage of the sodium supplement agent can match the battery operating voltage, thereby improving the coulombic efficiency and cycle performance of the battery. 2 / g, especially 1200-1500m 2 / g, which can further ensure that the first conductive agent and the sodium supplement agent have more contact sites, and help to further reduce the oxidation voltage of the sodium supplement agent.

[0073] In some embodiments, the first conductive agent includes at least one of a chain conductive agent or a grape-shaped conductive agent; optionally, the first conductive agent includes at least one of conductive carbon black and conductive graphite; optionally, the conductive carbon black includes at least one of acetylene black and Ketjen black.

[0074] It should be noted here that the grape-like conductive agent refers to a conductive agent whose microscopic particles are in the shape of bunches of grapes, such as conductive carbon black.

[0075] In the above scheme, by using at least one of a chain-shaped conductive agent or a grape-shaped conductive agent as the first conductive agent, the contact form between the first conductive agent and the sodium supplementer is point-to-point, which can ensure that the first conductive agent and the sodium supplementer have more contact sites, thereby improving the effect of the first conductive agent on the sodium supplementer; further, using at least one of conductive carbon black and conductive graphite, which are more convenient to obtain, as the first conductive agent, especially acetylene black or Ketjen black as the first conductive agent, is conducive to wide application in industry.

[0076] In some embodiments, when the first conductive agent includes conductive carbon black, the volume average particle size Dv50 of the first conductive agent is 20-60 nm. Optionally, the volume average particle size Dv50 of the first conductive agent is 30-50 nm.

[0077] In the above scheme, when conductive carbon black is used as the first conductive agent, the first conductive agent, that is, the volume average particle size Dv50 of the three materials is limited to 20-60nm, especially 30-50nm. The smaller particle size can make the first conductive agent contact with the sodium supplement more uniformly.

[0078] In some embodiments, when the first conductive agent includes conductive graphite, the volume average particle size Dv50 of the first conductive agent is 3-4 μm. Optionally, the volume average particle size Dv50 of the first conductive agent is 3.2-3.6 μm.

[0079] In the above scheme, when conductive graphite is used as the first conductive agent, by limiting the volume average particle size Dv50 of the first conductive agent, ie, conductive graphite, to 3-4 μm, especially 30-50 nm, the first conductive agent can be in contact with the sodium supplement more uniformly.

[0080] In some embodiments, the positive electrode film layer 123 further includes a second conductive agent, and the second conductive agent includes at least one of carbon fiber, carbon nanotube, ordered dielectric porous carbon, and graphene.

[0081] In the above scheme, when the specific surface area is 600-1600m 2 / g, especially 1200-1500m 2 When the first conductive agent of 100 g is added to the positive electrode film layer including the sodium supplement, the first conductive agent can reduce the oxidation potential of the sodium supplement so that the sodium supplement can function normally. By adding at least one of carbon fiber, carbon nanotube, ordered dielectric porous carbon, and graphene to the positive electrode film layer, the contact between the second conductive agent and the sodium supplement is point-line contact, which is conducive to further achieving voltage compatibility between the sodium supplement and the battery, thereby further improving the cycle performance and coulomb efficiency of the battery.

[0082] In some embodiments, when the second conductive agent includes carbon nanotubes, the carbon nanotubes have a length of 0.5-30 μm, a diameter of 2-15 nm, and a specific surface area of ​​not less than 200 m 2 / g. Optionally, the carbon nanotubes have a length of 0.5-10 μm, a diameter of 2-6 nm, and a specific surface area of ​​400-600 m 2 / g.

[0083] In some embodiments, when the second conductive agent includes ordered mesoporous carbon, the ordered mesoporous carbon has a pore size of 2-50 nm and a specific surface area of ​​500-1500 m 2 / g, optionally, the pore size of the ordered mesoporous carbon is 3.2-6.6nm, and the specific surface area is 800-1300m 2 / g. The ordered mesoporous carbon may include CMK-3 ordered mesoporous carbon and CMK-8 ordered mesoporous carbon.

[0084] In some embodiments, when the second conductive agent includes graphene, the graphene has a thickness of 0.6-4 nm and a sheet diameter of 0.5-5 μm. Alternatively, the graphene has a thickness of 1.5-3.2 nm and a sheet diameter of 0.5-3 μm.

[0085] It should be noted that the graphene thickness here can be the total thickness of multilayer graphene. Graphene is a layered material, and the thickness of a single-layer graphene is generally 0.3-0.4nm. The present application does not particularly limit the number of layers and the thickness of a single-layer graphene in graphene, and it is only necessary to ensure that the final graphene thickness is within the above range. For example, the final form of graphene can have 2-10 layers of single-layer graphene.

[0086] In the above scheme, when the first conductive agent and the second conductive agent are used together to reduce the oxidation potential of the sodium supplement, the cycle performance and coulombic efficiency of the battery can be further improved. The specific surface area of ​​the first conductive agent is 600-1600m 2 By limiting the performance parameters of the second conductive agent to the above range, the second conductive agent with better conductivity can better assist the first conductive agent, thereby further improving the performance of the battery.

[0087] In some embodiments, the mass ratio of the first conductive agent to the second conductive agent is 1-49. Optionally, the mass ratio of the first conductive agent to the second conductive agent is 4-9.

[0088] In the above scheme, in order to further improve the performance of the battery, a mixed first conductive agent and a second conductive agent are used in the battery film layer 123 to reduce the effective voltage of the sodium supplement. By limiting the mass ratio of the first conductive agent to the second conductive agent to 1-49, especially 4-9, the possibility of insufficient reduction of the effective voltage of the sodium supplement due to too little addition of the first conductive agent can be reduced.

[0089] In some embodiments, based on 100 parts by weight of the positive electrode film layer 123, the sum of the weight parts of the first conductive agent and the second conductive agent is 0.1-5 parts by weight. Optionally, the sum of the weight parts of the first conductive agent and the second conductive agent is 0.5-3 parts by weight.

[0090] In the above scheme, by limiting the conductive agent, that is, the sum of the masses of the first conductive agent and the second conductive agent, to 0.1%-5%, especially 0.5%-3% of the positive electrode film layer 123, the effective voltage of the sodium supplement can be effectively reduced so that the sodium supplement can improve the cycle performance and coulomb efficiency of the battery, and the energy density of the battery will not be affected by the excessive proportion of the first conductive agent and the second conductive agent.

[0091] In some embodiments, based on 100 parts by weight of the positive electrode film layer 123 , the weight of the sodium supplement is 0.5-20 parts by weight. Optionally, the weight of the sodium supplement is 1-5 parts by weight.

[0092] In the above scheme, by limiting the sodium supplement to 0.5%-20%, especially 1%-5% of the positive electrode film layer 123, the sodium loss in the battery can be effectively compensated without affecting the mass proportion of the positive electrode active material due to excessive proportion.

[0093] In some embodiments, the sodium supplement includes at least one of the following inorganic sodium supplements or organic sodium supplements, wherein the inorganic sodium supplement includes NaN3, Na2O2, Na2O, Na2CO3, NaNO2, NaBH4, NaNH2, Na2NiO2, NaCrO2, Na3P, Na2S, and the organic sodium supplement includes CH3COONa, C7H6NNaO2, C 10 H 12 N2Na4O8、C 14 H 18 N3Na5O 10 、Na a C b H c O d , 1≤a≤2, 2≤b≤6, 0≤c≤2, 2≤d≤6, optionally, the sodium supplement includes Na2C2O4.

[0094] In the above scheme, when at least one of the inorganic sodium supplement or the organic sodium supplement is used as the sodium supplement, the sodium supplement can make up for the irreversible sodium ion loss of the battery during the cycle, and does not affect the potential of the positive electrode active material, thereby improving the coulombic efficiency and cycle performance of the battery. In particular, when the sodium supplement includes Na2C2O4, Na2C2O4 decomposes and releases sodium ions and gas during battery formation and charging. The gas generated by the decomposition can be removed in the formation stage, and the sodium ions generated by the decomposition can effectively solve the problem of low battery energy density and poor cycle stability caused by irreversible consumption of sodium ions, that is, it can improve battery performance and have no adverse effects on the environment and the battery.

[0095] In some embodiments, the compaction density of the positive electrode sheet 121 is 1.2-2.8 g / cm 3 Optionally, the compaction density of the positive electrode sheet 121 is 1.6-2.3 g / cm 3 .

[0096] In the embodiment of the present application, the compaction density of the positive electrode sheet 121 is limited to 1.2-2.8 g / cm 3 , especially 1.6-2.3g / cm 3 , which helps to further improve the energy density of the battery.

[0097] In a possible implementation, the thickness of the positive electrode plate 121 is 50-90 μm. Optionally, the thickness of the positive electrode plate 121 is 65-80 μm.

[0098] In the embodiment of the present application, by limiting the thickness of the positive electrode plate 121 to 50-90 μm, especially 65-80 μm, it helps to further improve the energy density of the battery.

[0099] In one possible implementation, the coating weight of the positive electrode sheet 121 is 3.5-35 mg / cm 2 Optionally, the coating weight of the positive electrode sheet 121 is 10-25 mg / cm 2 .

[0100] In the embodiment of the present application, the coating weight of the positive electrode sheet 121 is limited to 3.5-35 mg / cm 2 , especially 10-25mg / cm 2 , which helps to further improve the energy density of the battery.

[0101] In some embodiments, the positive electrode active material includes Na x R y (PO4) z (P2O7) k , wherein 1≤x≤7, 1≤y≤4, 1≤z≤2, 1≤k≤4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W and Pb.

[0102] In the above scheme, by using the above material as the positive electrode active material, it helps to further improve the energy density of the battery.

[0103] It should be noted here that during the charge and discharge process of the battery, as Na ions are continuously deintercalated and consumed, the molar content of Na in the battery is different when it is discharged to different states. The above limitation on x includes the molar content of Na in different charge and discharge states of the battery.

[0104] In some embodiments, the positive electrode current collector 122 may be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0105] In some embodiments, the positive electrode active material may also include at least one of the following materials: sodium transition metal oxide, polyanionic compound and Prussian blue compound. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more.

[0106] In some embodiments, the transition metal in the sodium transition metal oxide may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. x MO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0<x≤1.

[0107] In some embodiments, the polyanionic compound may be a compound having sodium ions, transition metal ions and tetrahedral (YO4) n - A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si; n represents (YO4) n - valence state.

[0108] Polyanionic compounds can also be those with sodium ions, transition metal ions, tetrahedral (YO4) n - A class of compounds of anion units and halogen anions. The transition metal may include at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y may include at least one of P, S and Si, and n represents (YO4) n - valence state; the halogen may include at least one of F, Cl and Br.

[0109] Polyanionic compounds can also be sodium ions, tetrahedral (YO4) n - Anion unit, polyhedral unit (ZO y ) m + and an optional halogen anion. Y may include at least one of P, S and Si, and n represents (YO4) n - valence state; Z represents a transition metal, including at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; m represents (ZO y )m + valence state; the halogen may be at least one of F, Cl and Br.

[0110] Polyanionic compounds include NaFePO4, Na3V2(PO4)3 (sodium vanadium phosphate, abbreviated as NVP), Na4Fe3(PO4)2 (P2O7), NaM'PO4F (M' includes one or more of V, Fe, Mn and Ni) and Na3(VO y )2(PO4)2F 3-2y At least one of (0≤y≤1).

[0111] Prussian blue compounds can be sodium ions, transition metal ions and cyanide ions (CN - ). The transition metal may include at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. Prussian blue compounds are, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.

[0112] In some embodiments, the positive electrode film layer 123 may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0113] In some embodiments, the positive electrode plate 121 can be prepared in the following manner: the components for preparing the positive electrode plate 121, such as the positive electrode active material, the first conductive agent, the second conductive agent, the sodium supplement, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector 122, and after drying, cold pressing and other processes, the positive electrode plate 121 can be obtained.

[0114] The positive electrode plate 121 of the present application does not exclude other additional functional layers in addition to the positive electrode film layer 122. For example, in some embodiments, the positive electrode plate 121 of the present application also includes a conductive primer layer sandwiched between the positive electrode collector 122 and the positive electrode film layer 123 and disposed on the surface of the positive electrode collector 122. In other embodiments, the positive electrode plate 121 of the present application also includes a protective layer covering the surface of the positive electrode film layer.

[0115] [Negative electrode]

[0116] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0117] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0118] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.), or a current collector that combines support capabilities with functional elements, such as carbon cloth, carbon film, carbonaceous, porous current collector, alloy modified current collector, sodium-philic modified current collector.

[0119] In some embodiments, the negative electrode plate can be a rolled metal foil or a surface-coated inert layer of metal powder coated on a current collector; it can be a functional coated negative electrode, such as a carbon material coating (including single-arm, multi-arm conductive carbon tubes, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers, soft carbon and hard carbon, etc.), lithium-philic / sodium-philic metal composite coating, etc.

[0120] In some embodiments, the negative electrode plate is an alkali metal negative electrode. The alkali metal negative electrode may be an alkali metal layer pre-arranged on the surface of the current collector, or may be a negative electrode current collector, and an alkali metal layer is generated on the surface of the negative electrode current collector during the charge and discharge process. This application does not limit this.

[0121] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0122] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0123] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0124] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0125] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0126] [Electrolytes]

[0127] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0128] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0129] In some embodiments, as an example, the electrolyte salt may be a sodium salt, including but not limited to at least one of NaPF6, NaClO4, NaBCl4, NaSO3CF3 and Na(CH3)C6H4SO3. The sodium salts may be used alone or in combination of two or more.

[0130] In some embodiments, as an example, the organic solvent includes but is not limited to ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE) At least one. The above organic solvents can be used alone or in combination. Alternatively, two or more of the above organic solvents are used in combination.

[0131] In some embodiments, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0132] In some embodiments, as an example, the additive includes but is not limited to at least one of fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl carbonate (VEC), diethylene sulfate (DTD), propylene sulfate, vinyl sulfite (ES), 1,3-propane sultone (PS), 1,3-propylene sultone (PST), sulfonate cyclic quaternary ammonium salt, succinic anhydride, succinonitrile (SN), adiponitrile (AND), tris(trimethylsilyl) phosphate (TMSP), and tris(trimethylsilyl) borate (TMSB).

[0133] The electrolyte can be prepared according to conventional methods in the art. For example, an organic solvent, a sodium electrolyte salt, and an optional additive can be mixed uniformly to obtain an electrolyte. There is no particular restriction on the order of adding the materials. For example, an electrolyte sodium salt and an optional additive are added to an organic solvent and mixed uniformly to obtain an electrolyte; or, an electrolyte sodium salt is first added to an organic solvent, and then the optional additive is added to the organic solvent and mixed uniformly to obtain an electrolyte.

[0134] [Isolation film]

[0135] In some embodiments, the secondary battery further includes a separator. The separator is disposed between the positive electrode sheet 121 and the negative electrode sheet, and mainly serves to prevent the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The present application has no particular restrictions on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.

[0136] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0137] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0138] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0139] The present application has no particular restrictions on the shape of the battery cell, which can be cylindrical, square or any other shape. Figure 2 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0140] Figure 3 It is a schematic diagram of the structure of a battery cell of an embodiment of the present application. In some embodiments, the outer packaging may include a shell 11 and a cover plate 13. Among them, the shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet 121, the negative electrode sheet and the isolation film can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The number of electrode assemblies 12 contained in the battery cell 100 can be one or more, and those skilled in the art can choose according to specific actual needs.

[0141] In some embodiments, the battery cells 100 may also be assembled into a battery module. The battery module may contain one or more battery cells 100. The specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0142] Figure 4 is a schematic diagram of a battery according to one embodiment of the present application, Figure 5Schematic diagram of the structure of a battery according to one embodiment of the present application. Figure 4 and Figure 5 The battery 400 may include a battery box and a plurality of battery cells 100 disposed in the battery box. The battery box includes an upper box body 401 and a lower box body 402. The upper box body 401 can cover the lower box body 402 and form a closed space for accommodating the battery cells 100. The plurality of battery cells 100 may be arranged in the battery box in any manner.

[0143] In addition, the present application also provides an electric device, which includes at least one of the positive electrode sheet 121, battery cell 100 or battery provided in the present application. The positive electrode sheet 121, battery cell 100, or battery can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0144] For example, Figure 6 Schematic diagram of the structure of a vehicle according to an embodiment of the present application. Figure 6 As shown, vehicle 1 can be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A motor 500, a controller 600 and a battery 400 can be arranged inside the vehicle 1, and the controller 600 is used to control the battery 400 to power the motor 500. For example, a battery 400 can be arranged at the bottom, front or rear of the vehicle 1. The battery 400 can be used to power the vehicle 1. For example, the battery 400 can be used as an operating power source for the vehicle 1, for the circuit system of the vehicle 1, for example, for the working power requirements of the vehicle 1 during startup, navigation and operation. In another embodiment of the present application, the battery 400 can not only be used as an operating power source for the vehicle 1, but also as a driving power source for the vehicle 1, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1.

[0145] As the electrical device, the positive electrode sheet 121, the battery cell 100 or the battery 400 can be selected according to its usage requirements.

[0146] The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the electric device's requirements for high power and high energy density of the battery, a battery cell 100 or a battery 400 may be used.

[0147] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and the battery cell 100 may be used as a power source.

[0148] [Example]

[0149] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0150] [Example 1]

[0151] 1). Preparation of sodium ion batteries

[0152] 1.1) Preparation of positive electrode: Weigh the positive electrode active material Na4Fe3(PO4)2(P2O7), sodium supplement Na2C2O4, first conductive carbon black, second conductive carbon nanotubes, acetylene black, and binder polyvinylidene fluoride (PVDF) in a mass ratio of 90%: 3%: 4%: 0.5%: 1%: 1.5%, then add N-methylpyrrolidone (NMP) to adjust to a slurry state, use a scraper to evenly coat it on the surface of the positive electrode current collector Al foil, place it in a vacuum drying oven at 110°C and dry it for 5 to 6 hours, then dry, cold press, and cut to obtain the positive electrode sheet. Among them, the specific surface area of ​​the first conductive carbon black is 1000m 2 / g, the weight of the first conductive agent is 4 parts by weight, and the volume average particle size Dv50 is 30nm; the length of the second conductive agent carbon nanotube is 2μm, the diameter is 3nm, and the specific surface area is 400m 2 / g, the weight portion of the second conductive agent is 0.5 weight portion, and the mass ratio of the first conductive agent to the second conductive agent is 8; the sodium supplementer is Na2C2O4, and the weight portion of the sodium supplementer is 3 weight portions.

[0153] 1.2) Preparation of negative electrode: artificial graphite, conductive agent acetylene black, binder styrene butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC) are mixed in a proper amount of deionized water solvent system at a weight ratio of 97.5%:0.7%:1.8%:1% to obtain the negative electrode active material, and the negative electrode active material is coated on Cu foil, and then dried, cold pressed, and cut to obtain the negative electrode sheet.

[0154] 1.3). Preparation of diaphragm: PE porous polymer film is used as the isolation membrane.

[0155] 1.4). Electrolyte: Dissolve EC / EMC / DMC in 1M NaPF6 at a volume ratio of 1:1:1 and stir evenly.

[0156] 1.5) Assembly: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is in the middle of the positive and negative electrodes to play a role of isolation, and wind them to get the electrode assembly, and add electrolyte. Then hot press at 100℃ and 250MPa for 2min to get the lithium-ion battery.

[0157] [Example 2]

[0158] The preparation of the sodium ion battery of Example 2 is basically the same as that of Example 1, except that the specific surface area of ​​the first conductive agent, the conductive carbon black, is 600 m 2 / g.

[0159] [Example 3]

[0160] The preparation of the sodium ion battery of Example 3 is basically the same as that of Example 1, except that the specific surface area of ​​the first conductive agent, the conductive carbon black, is 1200 m 2 / g.

[0161] [Example 4]

[0162] The preparation of the sodium ion battery of Example 4 is basically the same as that of Example 1, except that the specific surface area of ​​the first conductive agent, the conductive carbon black, is 1500 m 2 / g.

[0163] [Example 5]

[0164] The preparation of the sodium ion battery of Example 5 is basically the same as that of Example 1, except that the specific surface area of ​​the first conductive agent, the conductive carbon black, is 1600 m 2 / g.

[0165] [Example 6]

[0166] The preparation of the sodium ion battery of Example 6 is basically the same as that of Example 1, except that the first conductive agent is Ketjen black.

[0167] [Example 7]

[0168] The preparation of the sodium ion battery of Example 7 is basically the same as that of Example 1, except that the first conductive agent is conductive graphite.

[0169] [Example 8]

[0170] The preparation of the sodium ion battery of Example 8 is basically the same as that of Example 7, except that the specific surface area of ​​the first conductive agent is 1200 m 2 / g.

[0171] [Example 9]

[0172] The preparation of the sodium ion battery of Example 9 is basically the same as that of Example 1, except that there is no second conductive agent in the positive electrode plate, and the mass ratio of the positive electrode active material Na4Fe3(PO4)2(P2O7), the sodium supplement Na2C2O4, the first conductive agent conductive carbon black, acetylene black, and the binder polyvinylidene fluoride (PVDF) is 90.5%:3%:4%:1%:1.5%.

[0173] [Example 10]

[0174] The preparation of the sodium ion battery of Example 10 is basically the same as that of Example 1, except that the parameters of the second conductive agent carbon nanotubes are different, wherein the parameters of the second conductive agent are: length: 2 μm, diameter: 3 nm, BET: 500 m 2 / g.

[0175] [Example 11]

[0176] The preparation of the sodium ion battery of Example 11 is basically the same as that of Example 1, except that the second conductive agent is CMK-3 ordered mesoporous carbon, wherein the parameters of the second conductive agent are: pore size: 5nm, BET: 600m 2 / g.

[0177] [Example 12]

[0178] The preparation of the sodium ion battery of Example 12 is basically the same as that of Example 1, except that the weight proportion of the first conductive agent is 2 parts by weight; the mass ratio of Na4Fe3(PO4)2(P2O7), sodium supplement Na2C2O4, first conductive agent conductive carbon black, second conductive agent carbon nanotubes, acetylene black, and binder polyvinylidene fluoride (PVDF) is 92%:3%:2%:0.5%:1%:1.5%, wherein the weight ratio of the first conductive agent to the second conductive agent is 4.

[0179] [Example 13]

[0180] The preparation of the sodium ion battery of Example 13 is basically the same as that of Example 1, except that the weight portion of the second conductive agent is 1 weight portion; the mass ratio of Na4Fe3(PO4)2(P2O7), sodium supplement Na2C2O4, first conductive agent conductive carbon black, second conductive agent carbon nanotubes, acetylene black, and binder polyvinylidene fluoride (PVDF) is 91.5%:3%:2%:1%:1%:1.5%, wherein the weight ratio of the first conductive agent to the second conductive agent is 2.

[0181] [Example 14]

[0182] The preparation of the sodium ion battery of Example 14 is basically the same as that of Example 1, except that the positive electrode active material Na4Fe3(PO4)2(P2O7) is replaced by Na4Mg3(PO4)2(P2O7).

[0183] [Example 15]

[0184] The preparation of the sodium ion battery of Example 15 is basically the same as that of Example 1, except that the positive electrode active material Na4Fe3(PO4)2(P2O7) is replaced by Na3V2(PO4)3.

[0185] [Example 16]

[0186] The preparation of the sodium ion battery of Example 16 is basically the same as that of Example 1, except that the sodium supplement is Na2C4O4.

[0187] [Example 17]

[0188] The preparation of the sodium ion battery of Example 17 is basically the same as that of Example 1, except that the weight portion of the sodium supplement is 0.5 weight portion, and the mass ratio of Na4Fe3(PO4)2(P2O7), sodium supplement Na2C2O4, the first conductive agent conductive carbon black, the second conductive agent carbon nanotubes, acetylene black, and the binder polyvinylidene fluoride (PVDF) is 92.5%: 0.5%: 4%: 0.5%: 1%: 1.5%.

[0189] [Example 18]

[0190] The preparation of the sodium ion battery of Example 18 is basically the same as that of Example 1, except that the weight of the sodium supplement is 6 parts by weight, and the mass ratio of Na4Fe3(PO4)2(P2O7), sodium supplement Na2C2O4, the first conductive agent conductive carbon black, the second conductive agent carbon nanotubes, acetylene black, and the binder polyvinylidene fluoride (PVDF) is 87%: 6%: 4%: 0.5%: 1%: 1.5%.

[0191] [Comparative Example 1]

[0192] The preparation of the sodium ion battery of Comparative Example 1 is basically the same as that of Example 1, except that the components of the positive electrode plate are Na4Fe3(PO4)2(P2O7), the first conductive agent conductive carbon black, acetylene black, and the binder polyvinylidene fluoride (PVDF). The mass ratio is 93.5%:4%:1%:1.5%; and the specific surface area of ​​the first conductive agent conductive carbon black is 400m 2 / g.

[0193] [Comparative Example 2]

[0194] The preparation of the sodium ion battery of Comparative Example 2 is basically the same as that of Comparative Example 1, except that the specific surface area of ​​the first conductive agent, the conductive carbon black, is 1000 m 2 / g.

[0195] [Comparative Example 3]

[0196] The preparation of the sodium ion battery of Comparative Example 3 is basically the same as that of Example 1, except that the components of the positive electrode plate are Na4Fe3(PO4)2(P2O7), sodium supplement Na2C2O4, first conductive agent conductive carbon black, acetylene black, and binder polyvinylidene fluoride (PVDF). The mass ratio is 90.5%: 3%: 4%: 1%: 1.5%; and the specific surface area of ​​the first conductive agent conductive carbon black is 400m 2 / g.

[0197] [Comparative Example 4]

[0198] The preparation of the sodium ion battery of Comparative Example 4 is basically the same as that of Example 1, except that the specific surface area of ​​the first conductive agent, the conductive carbon black, is 400 m 2 / g, the parameters of the second conductive agent carbon nanotube are: length: 0.4μm, diameter: 1nm, BET: 100m 2 / g.

[0199] 2. Performance characterization of sodium ion battery positive electrode

[0200] 2.1) Measurement of material specific surface area: You can refer to GB / T 19587-2004 "Gas adsorption BET method for determination of specific surface area of ​​solid substances", GB / T 13390-2004 "Determination of specific surface area of ​​metal powders - Nitrogen adsorption method" or GB / T7702.20-2008 "Test method for specific surface area of ​​coal-based granular activated carbon", and use any BET tester on the market for testing.

[0201] 2.2) Measurement of volume average particle size Dv50: It can be tested with a laser particle size analyzer (such as Master Size 3000) according to GB / T 19077-2016 particle size distribution laser diffraction method.

[0202] 2.3) Measurement of compaction density: For details, refer to GB / T 24533-2009. Take a certain amount of powder and put it in a special compaction mold, then put the mold on the compaction density instrument, weigh the weight of the powder m, and set the pressure to 400kN. The thickness (thickness after unloading) and volume v of the powder can be read on the equipment, and the compaction density can be calculated by ρ=m / v.

[0203] Table 1 Specific experimental parameters of Examples 1-18 and Comparative Examples 1-4

[0204]

[0205]

[0206] 3. Performance Characterization of Sodium Ion Batteries

[0207] 3.1) Test of the first coulombic efficiency: Under normal temperature conditions, charge to 3.9V at a constant current of 1 / 3C, then charge at a constant voltage of 3.9V until the current drops to 0.05C, and obtain the first charging capacity Cc1; then discharge to 1.5V at a constant current of 1 / 3C, and obtain the first discharge capacity Cd1. The first coulombic efficiency of the battery = Cd1 / Cc1. Please refer to Table 2 for the measurement results.

[0208] 3.2) Cycle performance test: At 45°C, keep the battery charge and discharge voltage range at 1.5-3.9V, cycle at 1C current density, and record the capacity retention rate after 200 cycles of the battery. The test results are shown in Table 2.

[0209] Table 2 Performance of Examples 1-18 and Comparative Examples 1-4

[0210]

[0211]

[0212] It can be seen from Comparative Examples 1 and 3 that adding a sodium supplement to a battery can improve the cycle performance and coulombic efficiency of the battery to a certain extent.

[0213] According to Examples 1-16 and Comparative Examples 1-3, it can be seen that adding a sodium supplement and adding a specific surface area of ​​not less than 600 m 2 / g of the first conductive agent, the first conductive agent enables the sodium supplement agent to fully play its role, and can significantly improve the cycle performance and coulomb efficiency of the battery.

[0214] According to Examples 1-5, 7-8 and Comparative Examples 3-4, it is known that when a specific surface area of ​​600-1600 m 2 / g, especially 1200-1500m 2 / g of the first conductive agent is beneficial to improving the cycle performance and coulombic efficiency of the battery.

[0215] According to Examples 1, 6, and 7, the specific surface area is not less than 600 m 2 / g of various conductive agents can play the role of sodium supplement to improve the cycle performance and coulombic efficiency of the battery.

[0216] It can be seen from Examples 1 and 9 that adding a second conductive agent to the battery is beneficial to further improving the coulombic efficiency of the battery.

[0217] According to Examples 1, 9-11, a variety of second conductive agents with good conductivity can assist the first conductive agent to further improve the cycle performance and coulombic efficiency of the battery.

[0218] According to Examples 1, 12-13, appropriately increasing the weight ratio of the first conductive agent to the second conductive agent, especially limiting the weight ratio of the first conductive agent to the second conductive agent to 4-9, is beneficial to further improve the cycle performance and coulombic efficiency of the battery.

[0219] It can be seen from Examples 1, 14-15 that a variety of positive electrode active materials are applicable to the technical solution of the present application.

[0220] According to Examples 1 and 16, various sodium supplements can improve the cycle performance and coulombic efficiency of the battery.

[0221] According to Examples 1 and 17-18, by maintaining the weight of the sodium supplement at 0.5-20 parts by weight, especially 1-5 parts by weight, the battery can have both good cycle performance and coulombic efficiency.

[0222] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the implementation methods that have the same structure as the technical idea and play the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode sheet, It is characterized in that include: A positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector; The positive electrode film layer includes a positive electrode active material, a sodium supplement agent, and a first conductive agent; Wherein, the specific surface area of ​​the first conductive agent is not less than 600m 2 / g.

2. The positive electrode sheet according to claim 1, It is characterized in that The specific surface area of ​​the first conductive agent is 600-1600m 2 / g, optionally, the specific surface area of ​​the first conductive agent is 1200-1500m 2 / g.

3. The positive electrode sheet according to claim 2, It is characterized in that The first conductive agent includes at least one of a chain-shaped conductive agent or a grape-shaped conductive agent; Optionally, the first conductive agent includes at least one of conductive carbon black and conductive graphite; Optionally, the conductive carbon black includes at least one of acetylene black and Ketjen black.

4. The positive electrode sheet according to claim 2 or 3, It is characterized in that In the case where the first conductive agent includes conductive carbon black, the volume average particle size Dv50 of the first conductive agent is 20-60 nm. Optionally, the volume average particle size Dv50 of the first conductive agent is 30-50 nm.

5. The positive electrode sheet according to claim 3 or 4, It is characterized in that In the case where the first conductive agent includes conductive graphite, the volume average particle size Dv50 of the first conductive agent is 3-4 μm. Optionally, the volume average particle size Dv50 of the first conductive agent is 3.2-3.6 μm.

6. The positive electrode sheet according to any one of claims 2 to 5, It is characterized in that The positive electrode film layer also includes a second conductive agent, which includes at least one of carbon fiber, carbon nanotube, ordered mesoporous carbon, and graphene.

7. The positive electrode sheet according to claim 6, It is characterized in that The second conductive agent satisfies at least one of the following conditions: (1) In the case where the second conductive agent includes the carbon nanotube, the carbon nanotube has a length of 0.5-30 μm, a diameter of 2-15 nm, and a specific surface area of ​​not less than 200 m 2 / g, optionally, the carbon nanotubes have a length of 0.5-10 μm, a diameter of 2-6 nm, and a specific surface area of ​​400-600 m 2 / g; (2) When the second conductive agent includes the ordered mesoporous carbon, the pore size of the ordered mesoporous carbon is 2-50 nm, and the specific surface area is 500-1500 m 2 / g, optionally, the ordered mesoporous carbon has a pore size of 3.2-6.6 nm and a specific surface area of ​​800-1300 m 2 / g; (3) When the second conductive agent includes the graphene, the graphene has a thickness of 0.6-4 nm and a sheet diameter of 0.5-5 μm. Optionally, the graphene has a thickness of 1.5-3.2 nm and a sheet diameter of 0.5-3 μm.

8. The positive electrode sheet according to claim 6 or 7, It is characterized in that The mass ratio of the first conductive agent to the second conductive agent is 1-49. Optionally, the mass ratio of the first conductive agent to the second conductive agent is 4-9.

9. The positive electrode sheet according to any one of claims 6 to 8, It is characterized in that Based on 100 parts by weight of the positive electrode film layer, the sum of the weight of the first conductive agent and the second conductive agent is 0.1-5 parts by weight. Optionally, the sum of the weight of the first conductive agent and the second conductive agent is 0.5-3 parts by weight.

10. The positive electrode sheet according to any one of claims 1 to 9, It is characterized in that Based on 100 parts by weight of the positive electrode film layer, the weight of the sodium supplement is 0.5-20 parts by weight. Optionally, the weight of the sodium supplement is 1-5 parts by weight.

11. The positive electrode sheet according to any one of claims 1 to 10, It is characterized in that The sodium supplement includes at least one of the following inorganic sodium supplement or organic sodium supplement, wherein the inorganic sodium supplement includes NaN 3 、Na 2 O 2 、Na 2 O、Na 2 CO 3 、NaNO 2 , NaBH 4 、NaNH 2 、Na 2 NiO 2 、NaCrO 2 、Na 3 P, Na 2 S, the organic sodium supplement includes CH 3 CO`ONa、C 7 H 6 NNaO 2 , C 10 H 12 N 2 Na 4 O 8 , C 14 H 18 N 3 Na 5 O 10 、Na a C b H c O d , 1≤a≤2, 2≤b≤6, 0≤c≤2, 2≤d≤6, optionally, the sodium supplement includes Na 2 C 2 O 4 .

12. The positive electrode sheet according to any one of claims 1 to 11, It is characterized in that The compaction density of the positive electrode sheet is 1.2-2.8 g / cm 3 Optionally, the compaction density of the positive electrode sheet is 1.6-2.3 g / cm 3 .

13. The positive electrode sheet according to any one of claims 1 to 12, It is characterized in that The thickness of the positive electrode plate is 50-90 μm. Optionally, the thickness of the positive electrode plate is 65-80 μm.

14. The positive electrode sheet according to any one of claims 1 to 13, It is characterized in that The coating weight of the positive electrode sheet is 3.5-35 mg / cm 2 Optionally, the coating weight of the positive electrode sheet is 10-25 mg / cm 2 .

15. The positive electrode sheet according to any one of claims 1 to 14, It is characterized in that The positive electrode active material includes Na x R y (PO 4 ) z (P 2 O 7 ) k , wherein 1≤x≤7, 1≤y≤4, 1≤z≤2, 1≤k≤4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W and Pb.

16. A battery cell, It is characterized in that Comprising the positive electrode sheet as claimed in any one of claims 1 to 15.

17. The battery cell according to claim 16, It is characterized in that The battery cell further comprises a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector, and the negative electrode film layer comprises a conductive agent.

18. A battery, It is characterized in that Comprising the battery cell as claimed in claim 16 or 17.

19. An electrical device, It is characterized in that Comprising the battery of claim 18.

Citation Information

Patent Citations

  • Prussian blue-based sodium ion total battery and production method thereof

    CN113054163A

  • Composite sodium supplement additive and application thereof in sodium ion battery

    CN113113681A

  • Sodium ion positive electrode plate, preparation method thereof and sodium ion battery

    CN115425173A

  • Sodium-ion battery positive plate, preparation method thereof and sodium-ion battery

    CN116190570A

  • Negative electrode composite for all-solid sodium ion battery, and use thereof

    JP2023079115A

Cited By

  • Sodium supplement additive, positive pole piece and sodium ion battery

    CN120072938A

  • A sodium ion battery positive electrode sheet coated with a sodium-chromium-oxide sodium-supplementing substrate and a preparation method thereof

    CN122716290A